Sustaining Mana in Mate Wareware Care: Whānau Perspectives - Kirsten Robertson (Kāi Tahu); Tui Kaitai-Martin (Kāi Tahu); Rob Thomson; Diane Ruwhiu (Ngā Puhi); Maree Thyne (International Journal of Environmental Research and Public Health, 2026)
Māori experience inequities in the recognition of mate wareware and in access to dementia and aged care support in Aotearoa New Zealand. Less is known about how whānau experience supporting a whānau member with mate wareware, what support they find helpful, and what they consider important for mate wareware-friendly communities. This kaupapa Māori qualitative study involved a co-design phase with seven kaumātua, which informed the study questions and whānau hui guide, followed by ten in-depth whānau Māori hui involving 12 individual participants; the whānau hui formed the analytic dataset. Whānau hui data were analysed using reflexive thematic analysis. Four interconnected themes were developed: delayed recognition; whānau caregiving as collective strength alongside concentrated responsibility; sustaining wairua, identity, and belonging; and care transitions and structural barriers. Interpreted together, these themes informed a four-condition account of mana-preserving care, in which mana may be sustained or eroded through interactions among recognition and knowledge, whānau caregiving, wairua, identity and belonging, and service and institutional conditions at transitions. Where continuity fragmented, whānau frequently undertook integrative work to bridge gaps across people, places, culture, and services. The findings point to earlier mate wareware information and support through Māori-facilitated and community-based approaches, support that recognises concentrated caregiving responsibility, continuity across services and transitions, and routine practices that embed tikanga, while reducing reliance on whānau to compensate for fragmentation.